2022
DOI: 10.14218/jcth.2021.00586
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma in Non-alcoholic Fatty Liver Disease: Current Progresses and Challenges

Abstract: The rising global prevalence of metabolic diseases has increased the prevalence of non-alcoholic fatty liver disease (NAFLD), leading to an increase in cases of NAFLD-related hepatocellular carcinoma (HCC). To provide an updated literature review detailing epidemiology, risk factors, pathogenic pathways, and treatment strategies linked to NAFLD-related HCC, we conducted a literature search on PubMed from its inception to December 31, 2021. About 25% of the global population suffers from NAFLD. The annual incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…All five of those studies reported similar OS between patients with NAFLD- or NASH-related HCC and patients with HCC related to viral hepatitis or alcohol ( Table S2 ). However, other studies found that lenvatinib treatment may lead to better OS, while immune checkpoint inhibitors may lead to worse OS when treating NAFLD-related HCC compared with HCC of other aetiologies 67 , 68 . In addition to hepatectomy, liver transplantation and radiofrequency ablation can be applied as radical therapies against HCC.…”
Section: Discussionmentioning
confidence: 97%
“…All five of those studies reported similar OS between patients with NAFLD- or NASH-related HCC and patients with HCC related to viral hepatitis or alcohol ( Table S2 ). However, other studies found that lenvatinib treatment may lead to better OS, while immune checkpoint inhibitors may lead to worse OS when treating NAFLD-related HCC compared with HCC of other aetiologies 67 , 68 . In addition to hepatectomy, liver transplantation and radiofrequency ablation can be applied as radical therapies against HCC.…”
Section: Discussionmentioning
confidence: 97%
“…[52,53] In the visualization analysis, hepatocellular carcinoma has received much attention as an important class of cancer cell lines that have been studied in recent years, and the liver itself, as a major lipid-and cholesterol-metabolizing organ, has been closely associated with cancer in the known pathways of the LXR mechanism. Notably, with the overall improvement of global health conditions, the proportion of hepatocellular carcinoma caused by etiologies such as hepatitis and aflatoxin has declined, replaced by hepatocellular carcinoma caused by high-fat factors such as nonalcoholic fatty liver disease, [54] Nonalcoholic fatty liver disease is also reflected as an important cluster in the term clustering. Many studies have revealed the crosstalk mechanism between multiple signaling pathways and LXR in hepatocellular carcinoma progression, such as the crosstalk of LXR by TGFβ under the Snail factor contributes to the activation of mesenchymal transition process by hepatocyte apoptosis, which enhances the aggressiveness of hepatocellular carcinoma [55] ; LXR activates and weakens the phosphorylation process of protein kinase and induces the accumulation of ABCG1 to promote efflux cholesterol and reduce the function of lipid rafts, thereby leading to the inactivation of Akt pathway and interfering with the progression of hepatocellular carcinoma through PI3K/Akt pathway.…”
Section: Advances and Frontiers In Cancer Researchmentioning
confidence: 99%
“…In patients with NAFLD the prevalence of HCC is 2.6%, four times higher in males than females [ 54 , 82 ]. Although several factors are decisive in the onset of HCC, such as advanced age, pro-inflammatory cytokines, the action of adipokines, smoking habits, the presence of obesity and T2D, a key role is certainly played by sexual hormones [ 83 , 84 ]. Oestrogens play a protective role against liver disease, but, as demonstrated by the epidemiological trend of liver cirrhosis and HCC, this protection is drastically reduced in women aged >65 years [ 85 ].…”
Section: Sex and Gender Differences In Chronic Liver Diseases And T2dmentioning
confidence: 99%